Magnetorefractive effect in metallic Co/Pt nanostructures - А. N. Yurasov; D. A. Sayfulina; Т. N. Bakhvalova (Российский технологический журнал)
Objectives. To carry out a theoretical investigation of the features of magnetorefractive effect for metal-to-metal nanostructures. This study uses the example of multilayer Co/Pt nanostructures (ferromagnetic metal–paramagnetic metal) with a different ratio of ferromagnetic and paramagnetic phases in the visible and near-infrared (IR) spectral regions.Methods. The dependence was expressed explicitly using the basic formulas for permittivity, refraction and extinction coefficients, and optical conductivity. This then confirms the common nature of these two effects. The magnetorefractive effect for s-polarization of light was calculated using Fresnel formulas for a three-layer structure. This took into account the thickness of the samples and the influence of the substrate. Effective medium methods were used to calculate the dielectric permittivity of materials. Since the average range of cobalt concentrations was being studied, the Bruggeman approximation was used to establish the effective permittivity of nanostructures. The reflection coefficient at normal incidence was calculated for all nanostructures.Results. Since the permittivity of inhomogeneous samples was replaced by a common effective parameter depending on the permittivity of each component, we were able to apply the Drude–Lorentz theory for conductors in a high-frequency alternating field and then estimate the parameters of the electronic structure of the samples being studied. Plasma and relaxation frequencies were calculated for each sample. This made it possible for the number of free electrons to be estimated and scattering in nanostructures to be investigated.Conclusions. It was shown that Langmuir shielding can be observed in the given energy range in the IR region of the spectrum. The calculated values correlate well with the experimental data.